Analisis Pengaruh Lingkungan Kerja, Kompensasi dan Motivasi Terhadap Kinerja Guru Pada SD-SMP Strada Kampung Sawah Bekasi - Mateus Maryo Untoro; Rakhmat; Andi (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
Education has a role in creating quality and competent human resources in accordance with the demands of development in the digitalization 4.0 era. The role of the teacher as an educator is expected to be able to support in creating a quality and competent generation. Responsibilities given properly in accordance with the rights received by the teacher. Several factors can affect teacher performance including: work environment, compensation and motivation. From the point of view of human resource management, these three factors play an important role in improving performance. The purpose of this study was to determine the effect of the work environment, compensation and motivation on teacher performance at Strada Kampung Sawah Elementary School and Strada Kampung Sawah Junior High School. The method used is quantitative analysis which is qualitativeized using the SPSS version 26 analysis tool. The results of the simple correlation test show that the r-count in the work environment is 0.474, compensation is 0.457, and motivation is 0.371, all three are greater than the r-table of 0.3494. These results indicate that the three variables have a relationship or correlation with performance variables. Multiple linear regression test obtained the equation Y = 25.132 + 0.217 X1 + 0.159 X2 + 0.285 X3. Based on the results of the t-test hypothesis, partially the work environment affects teacher performance with t-count 3.030 > t-table 2.045, compensation affects teacher performance with t-count 2.180 > t-table 2.045, and motivation influences teacher performance with t-count 3.040 > t-table 2.045. Meanwhile, based on the results of the simultaneous f-test hypothesis, work environment, compensation and motivation affect teacher performance with f-count 9.253 > f-table 2.94. It is hoped that a well-managed physical and non-physical work environment can be maintained and improved so that teachers can feel safe and comfortable while working. Compensation provided financially and non-financially in accordance with expectations and can adapt to current economic changes will be able to increase motivation and enthusiasm for work. Forms of intrinsic and extrinsic motivation that have been well developed are expected to be maintained and improved to improve the work results and work attitudes of Strada Kampung Sawah Elementary School and Strada Kampung Sawah Junior High School teachers.